Sustainable Human Resource Management and Employee Retention: Understanding the Mediating Mechanisms of Organizational Commitment and Job Satisfaction - Zaidan Nawawi; Telly Pauline Ulviana Siwi; Dasmadi Dasmadi (Yayasan Darussalam Bengkulu, 2025)
Employee retention has become a strategic challenge for organizations seeking to maintain competitiveness in an increasingly dynamic and sustainability-oriented business environment. Sustainable Human Resource Management (SHRM) has emerged as a critical approach that integrates economic, social, and employee well-being objectives to enhance long-term organizational performance. This study examines the effect of SHRM on employee retention by investigating the mediating roles of organizational commitment and job satisfaction. A quantitative research design was employed using a cross-sectional survey of employees from various organizations. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess both direct and indirect relationships among the proposed constructs. The findings indicate that SHRM has a significant positive effect on organizational commitment, job satisfaction, and employee retention. Furthermore, organizational commitment and job satisfaction significantly mediate the relationship between SHRM and employee retention, suggesting that sustainable HR practices strengthen employees' emotional attachment and satisfaction, which subsequently increase their intention to remain with the organization. These results extend the Sustainable Human Resource Management literature by providing empirical evidence of the psychological mechanisms linking sustainable HR practices to employee retention. The study offers practical implications for managers by emphasizing the importance of implementing sustainable HR policies that foster a supportive work environment, enhance employee well-being, and cultivate long-term organizational commitment to reduce turnover and improve organizational sustainability.